2022
DOI: 10.3389/fimmu.2022.831822
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuity of Peptides Presented in HLA-DP Molecules from Different Immunogenicity Groups Is Associated With T-Cell Cross-Reactivity

Abstract: In the context of HLA-DP-mismatched allogeneic stem cell transplantation, mismatched HLA-DP alleles can provoke profound allo-HLA-DP-specific immune responses from the donor T-cell repertoire leading to graft-versus-leukemia effect and/or graft-versus-host disease in the patient. The magnitude of allo-HLA-DP-specific immune responses has been shown to depend on the specific HLA-DP disparity between donor and patient and the immunogenicity of the mismatched HLA-DP allele(s). HLA-DP peptidome clustering (DPC) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Of note, these limitations are also affecting state-of-the-art MHC-II ligand predictors (see examples in Figures 4B, S4B and S6). As such our results provide both a refined view of the main MHC-II binding specificities, in line with the recent classification proposed for HLA-DP alleles (Laghmouchi et al, 2022; Meurer et al, 2021), and a robust implementation of these observations into an accurate MHC-II ligand prediction tool (MixMHC2pred-2.0).…”
Section: Discussionsupporting
confidence: 85%
“…Of note, these limitations are also affecting state-of-the-art MHC-II ligand predictors (see examples in Figures 4B, S4B and S6). As such our results provide both a refined view of the main MHC-II binding specificities, in line with the recent classification proposed for HLA-DP alleles (Laghmouchi et al, 2022; Meurer et al, 2021), and a robust implementation of these observations into an accurate MHC-II ligand prediction tool (MixMHC2pred-2.0).…”
Section: Discussionsupporting
confidence: 85%
“…The raw files were obtained from PRIDE (23) under the accession PXD030591 as provided by Laghmouchi et al . (22), subsequently, peptides were identified from each allele using MHCQuant (24) ( Material and Methods ). ( A ) The predictive accuracy of the four tools on elution data from proteins encoded by HLA-DP proteins (y-axis) where accuracy was measured using the area under the receiver operating curve AUC (ROC) (x-axis).…”
Section: Resultsmentioning
confidence: 99%
“…3. The third dataset (benchmarking-3) was assembled from an HLA-DP immunopeptidomic dataset obtained from Laghmouchi et al (22). The dataset contained 13 different immunopeptidomic datasets each of which was obtained from a different HLA-DP protein.…”
Section: Development Of Pia-m Architecturementioning
confidence: 99%
“…Each one of these TCE groups of DPB1 alleles is characterized by distinct structural features that differentiate one from the other group and influence the peptides bound to the DP protein. Most recently, the immunopeptidome of the alleles that belong to each one of these groups has been characterized (van Balen et al, 2020;Meurer et al, 2021;Laghmouchi et al, 2022). Considering that in our study of AD we have identified HLA-DPA1 and DPB1 alleles and specific residues relevant to the disease, we were interested to investigate as to whether any of the structural elements (alleles or residues) of the DP molecules correlated with the TCE groups, therefore, establishing a relationship between the DP structural elements of our study with the functional grouping of DPs including the peptide repertoire that characterizes each one of the TCE groups.…”
Section: Discussionmentioning
confidence: 99%